Perspektif Dokter dan Perawat Terkait Kolaborasi Bersama Apoteker Dalam Penanganan Hipertensi di Puskesmas Wilayah Kabupaten Lombok Tengah - Nia Mariana Siregar; Hanni Prihastuti Puspitasari; Wahyu Utami (Universitas Malahayati Lampung, 2024)
ABSTRACT Puskesmas is a primary healthcare facility that carries out chronic disease management by the healthcare team such as hypertension. The role of pharmacists in team collaboration includes managerial and clinical pharmacy aspects. However, doctors and nurses are still not fully aware of the role of pharmacists, especially in clinical pharmacy. This study aims to determine the perspectives of doctors, and nurses on the collaborative management of hypertension in primary healthcare centers across Central Lombok Regency. The method used in this study was observational qualitative with a maximum variation sampling technique. Data saturation was achieved after interviewing 18 participants from April to June 2023. Participants were pharmacists, doctors, and nurses who were responsible for managing hypertension in selected primary healthcare centers. The four themes followed a conceptual framework related to team readiness to make collaboration, including cognitive, affective/relational, behavioral, and leadership aspects. In general doctors and nurses were not aware of the pharmacist’s role in clinical pharmacy, although the communication within the team is going well. Team collaboration has not run optimally because each team member performs his role individually and not as a team. To collaborate, supporting facilities and media are needed along with directions from the head of primary healthcare centers as the team leader. From the perspective of doctors and nurses, efforts are needed to prepare a team to involve pharmacists in collaborating in the management of hypertension. Keywords: Perspective, Team Collaboration, Hypertension ABSTRAK Puskesmas merupakan fasilitas pelayanan kesehatan primer yang melaksanakan penanganan penyakit kronis salah satunya hipertensi dan membutuhkan tim perawatan kesehatan. Keterlibatan apoteker berperan dalam aspek manajerial dan farmasi klinik. Akan tetapi penelitian sebelumnya menunjukkan bahwa kolaborasi tidak berjalan optimal ketika dari perspektif tenaga kesehatan lain seperti dokter dan perawat kurang menyadari peran apoteker khususnya dalam melakukan aktivitas farmasi klinik. Menganalisis perspektif dokter dan perawat terkait keterlibatan apoteker berkolaborasi dalam penanganan hipertensi di puskemas wilayah Kabupaten Lombok Tengah. Observasional dan kualitatif dengan teknik maximum variation sampling. Data saturasi tercapai setelah wawancara kepada 18 informan pada bulan April-Juni 2023. Informan adalah dokter dan perawat yang bertanggungjawab dalam penanganan hipertensi di puskesmas. Empat tema sesuai dengan kerangka konseptual terkait kesiapan tim untuk berkolaborasi, meliputi: aspek kognitif, afektif/relasional, perilaku, dan kepemimpinan. Secara umum dokter dan perawat tidak mengetahui potensi apoteker dalam hal klinis walaupun komunikasi dalam tim berjalan baik. Kerjasama dalam tim sebatas melakukan perannya masing-masing dan berjalannya kolaborasi membutuhkan peran kepala puskesmas sebagai pemimpin tim. Dari perspektif dokter dan perawat dibutuhkan upaya mempersiapkan tim untuk melibatkan apoteker berkolaborasi dalam penanganan hipertensi. Kata Kunci: Perspektif, Kolaborasi Tim, Hipertensi